TINGKAT CEMARAN Staphylococcus aureus PADA IKAN ASIN DI PASAR TRADISIONAL KOTA KUPANG - Marlin Cindy Claudya Malelak; Diana A. Wuri; Elisabet Tangkonda (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Fish has become one of the favorite foodstuffs for Indonesian society. Like the other food commodities of animal origin, fish also has a perishable nature so it takes a good handling and processing, such as salting and drying which the result is known as salted fish. The processing of salted fish requires attention because there is a high risk of food poisoning hazard for food which the growth of normal flora are inhibited due to the enterotoxin of Staphylococcus aureus. This study aims to determine the contamination level of Staphylococcus aureus within the salted fish in the traditional markets in the city of Kupang. There were 18 samples of salted fishes used which consisted of 8 samples from Oesapa traditional market, 5 samples from Oeba traditional market and 5 samples from theInpres Naikoten traditional market. The sample inspection using the Plate Count method in order to spread. The results showed that the contamination level of all the salted fish samples have passed the maximum contamination limit of S. aureus based on the SNI No. 7388 : 2009 (1 x 103 CFU/g) with the value of the contamination level ranged from 3.4 x 103 CFU/g in the salted fish derived from Oeba traditional market to 1.4 x 106 CFU/g in the salted fish derived from the Inpres Naikoten market. The high value of the contamination level is related to several factors such as environment, storage time, sanitation and personal hygiene. Therefore, salted fish traded in traditional markets require attention to be safe and suitable for consumption.